An Islamic spiritual alternative to addiction treatment and recovery - Bensaid, Benaouda; Machouche, Salah; Tekke, Mustafa (Al-Jami'ah Research Centre, 2021)
The Islamic spirituality permeating the practice of Muslim religious beliefs, values, and norms, is positioned to play a pivotal role in addiction prevention, treatment, rehabilitation therapy and recovery of Muslim addicts. This study seeks to explore potential interconnections between spirituality, addiction treatments, recovery, and the ways and means with which Islamic spirituality may assist addicts in coping with inner urges, relapse, and recovery. This study seeks to lay the groundwork for future theoretical and empirical research on spirituality and addiction, the development of spirituality-based addiction programs, and the assessment of related current spiritual philosophies, methods, and strategies. This inquiry discusses spirituality as a source of meaning-making and purpose cultivation, self-discipline, motivation, support, reintegration, and related issues arising in these regards, and highlights the need for utilizing spirituality as a critical instrument in addiction treatment programs. Islamic spirituality however is neither – and should not be considered - a sole treatment scheme, nor does it appreciate absolute reliance on non-spiritual means of recovery in favor of positivistic empirical methods.